2007
DOI: 10.5194/hess-11-158-2007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological science and wetland restoration: some case studies from Europe

Abstract: Throughout the world, wetlands are increasingly being recognised as important elements of the landscape because of their high biodiversity and goods and services they provide to mankind. After many decades of wetland destruction and conversion, large areas of wetlands are now protected under the International Convention on Wetlands (Ramsar) and regional or national legislation such as the European Union Habitats Directive. In many cases, there is a need to restore the ecological character of the wetland throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 12 publications
0
75
0
Order By: Relevance
“…The equipment of ditch networks with hydraulic structures (e.g., buried pipes and weirs) that improve water storage capacity of the network (Acreman et al 2007;Sofia et al 2014) may attenuate floods downstream during extreme rain events. Equipped ditch networks are considered as one of the techniques permitting dynamic flood retention (Poulard et al 2008).…”
Section: Flood Regulationmentioning
confidence: 99%
“…The equipment of ditch networks with hydraulic structures (e.g., buried pipes and weirs) that improve water storage capacity of the network (Acreman et al 2007;Sofia et al 2014) may attenuate floods downstream during extreme rain events. Equipped ditch networks are considered as one of the techniques permitting dynamic flood retention (Poulard et al 2008).…”
Section: Flood Regulationmentioning
confidence: 99%
“…The existing publications on FPLs usually deal with natural valleys of large rivers in South America and North America (Lesack and Melack, 1995;Schemel et al, 2004;Williams et al, 2004;Acreman et al, 2007;Phlips et al, 2008;Wren et al, 2008;Alcântara et al, 2010;Affonso et al, 2011). The channels of the majority of European rivers were at some stage modified; this made floodplain lakes disappear.…”
Section: Discussionmentioning
confidence: 99%
“…Floodplain restoration schemes are thought to reduce flood risk as they reconnect the channel to its floodplain (Acreman et al, 2007), allowing water storage on the floodplain in flood expansion areas, which are commonly agricultural fields (Pivot et al, 2002). Interception ponds have been used at Nafferton Farm in the Tyne valley to store road runoff to benefit water quality (Jonczyk et al, 2008), but has also been shown how they have water quantity advantages at Belford in Northumberland .…”
Section: Wetlandsmentioning
confidence: 99%